Rejuvenasi Peraturan Pengelolaan Prekursor: Ratio Legis dan Efektivitas - Tahegga Primananda Alfath; Kristy Anita (University of Jember, Indonesia, 2022)
This legal research aims to examine the legal aspect ratio of legal instruments relating to pharmaceutical precursors as they relate to rejuvenation efforts; while at the same time reviewing based on the perspective of legal effectiveness on the regulation of pharmaceutical precursors. The results of this study state that the ratio of precursors to legislative regulation can be seen from three approaches, namely philosophical, juridical, and sociological. On the philosophical aspect, the 1945 Constitution provides an obligation to the government to provide welfare for matters related to health, the use of pharmaceutical precursors by the public. Then, from a juridical aspect, there are various legal products related to the management and utilization of pharmaceutical precursors; as the legal instruments are interrelated with each other. Sociologically, the illegal production and use of psychotropic substances through precursors will disrupt the economy, security and public health. However, the regulation on precursors has not been implemented in terms of structure, substance, effectiveness or culture; Thus, there are still many deviations in the management of precursors in the community. KEYWORDS: Rejuvenation, Pharmaceutical Precursors, Law Effectiveness